Pergunta
Multiply. (4sqrt (6)-2)(5sqrt (3)+4)
Solução
Verification of experts
4.7265 Voting
CintiaMestre · Tutor por 5 anos
Responder
To multiply the given expression, we will use the distributive property (also known as the FOIL method for binomials):
(4\sqrt{6} - 2)(5\sqrt{3} + 4)
First, we multiply the first terms:
4\sqrt{6} \cdot 5\sqrt{3} = 20\sqrt{18} = 20\sqrt{9 \cdot 2} = 20 \cdot 3\sqrt{2} = 60\sqrt{2}
Next, we multiply the outer terms:
4\sqrt{6} \cdot 4 = 16\sqrt{6}
Then, we multiply the inner terms:
-2 \cdot 5\sqrt{3} = -10\sqrt{3}
Finally, we multiply the last terms:
-2 \cdot 4 = -8
Now, we combine all the terms:
60\sqrt{2} + 16\sqrt{6} - 10\sqrt{3} - 8
Therefore, the final answer is:
60\sqrt{2} + 16\sqrt{6} - 10\sqrt{3} - 8
(4\sqrt{6} - 2)(5\sqrt{3} + 4)
First, we multiply the first terms:
4\sqrt{6} \cdot 5\sqrt{3} = 20\sqrt{18} = 20\sqrt{9 \cdot 2} = 20 \cdot 3\sqrt{2} = 60\sqrt{2}
Next, we multiply the outer terms:
4\sqrt{6} \cdot 4 = 16\sqrt{6}
Then, we multiply the inner terms:
-2 \cdot 5\sqrt{3} = -10\sqrt{3}
Finally, we multiply the last terms:
-2 \cdot 4 = -8
Now, we combine all the terms:
60\sqrt{2} + 16\sqrt{6} - 10\sqrt{3} - 8
Therefore, the final answer is:
60\sqrt{2} + 16\sqrt{6} - 10\sqrt{3} - 8
Clique para avaliar: